2021
DOI: 10.3390/ma14051181
|View full text |Cite
|
Sign up to set email alerts
|

Towards Selection Charts for Epoxy Resin, Unsaturated Polyester Resin and Their Fibre-Fabric Composites with Flame Retardants

Abstract: Epoxy and unsaturated polyester resins are the most used thermosetting polymers. They are commonly used in electronics, construction, marine, automotive and aircraft industries. Moreover, reinforcing both epoxy and unsaturated polyester resins with carbon or glass fibre in a fabric form has enabled them to be used in high-performance applications. However, their organic nature as any other polymeric materials made them highly flammable materials. Enhancing the flame retardancy performance of thermosetting poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 132 publications
0
17
0
Order By: Relevance
“…Different solutions have been tested in the literature. These solutions were recently reviewed by Ramadan et al, who even proposed a selection chart for polyester and their fibre-fabric composite [6]. Among the most-used FR additives in UPR, aluminum trihydroxide (ATH) has been the most investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Different solutions have been tested in the literature. These solutions were recently reviewed by Ramadan et al, who even proposed a selection chart for polyester and their fibre-fabric composite [6]. Among the most-used FR additives in UPR, aluminum trihydroxide (ATH) has been the most investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively expensive to other flame retardants [177]. Incompatibility of ammonium polyphosphate and melamine polyphosphate with some resins (e.g., epoxy), leading to phase separation [178].…”
Section: Type Of Fr Examples Of Compounds Mode Of Action Advantages D...mentioning
confidence: 99%
“…Several previous studies have revealed the effect of fire retardants on GFRP composites, both on their mechanical and physical properties [ 4 , 5 , 6 , 7 , 8 , 9 ]. The type of fire retardant used, as well as its load, significantly affects the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The type of fire retardant used, as well as its load, significantly affects the mechanical properties. In general, adding a fire retardant reduces mechanical properties [ 4 ]. The addition of ATH to GFRP as a filler has been observed to weaken tensile strength, which decreases due to poorer bonding between the filler powder, matrix, and the glass fiber used [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%